A Phase 1b trial of prexasertib in combination with chemoradiation in patients with locally advanced head and neck squamous cell carcinoma. (April 2021) - Yang, Eddy S.; Deutsch, Eric; Mehmet, Altan; Fayette, Jerome; TAO, Yungan; Nabell, Lisle; Spencer, Sharon A.; Wang, Xuejing A.; Spoljoric, Elizabeth A.; Zhang, Wei; Hynes, Scott M.; Decker, Rodney L.; et al.
Highlights: Results show potential sensitization of CHK1 inhibitor with RT or targeted agents. The safety profile observed is consistent with prior prexasertib studies. The PK of prexasertib is not affected by concomitant cisplatin or cetuximab. Abstract: Background and purpose: This study explored the feasibility of safely combining prexasertib, with cisplatin-radiotherapy (Part A) or cetuximab-radiotherapy (Part B) in patients with previously untreated, locoregionally advanced head and neck squamous cell carcinoma (HNSCC). Materials and methods: Escalating doses of prexasertib were administered in each combination using a modified Time-to-Event Continual Reassessment Method. Pharmacokinetic (PK) analysis was performed using standard non-compartmental methods of analysis. Antitumor activity was evaluated using RECIST version 1.1. Results: In Part A, 7 patients received 20 mg/m 2 prexasertib and cisplatin-radiotherapy. This dose exceeded the maximum tolerated dose (MTD); no other prexasertib dose was assessed. In Part B, 18 patients received prexasertib (20–40 mg/m 2 ) and cetuximab-radiotherapy. The 30 mg/m 2 dose of prexasertib was determined as the MTD. Febrile neutropenia was the dose-limiting toxicity in each arm. Most common treatment-emergent adverse events with both combinations were neutropenia, thrombocytopenia, dysphagia, stomatitis, dry mouth, anemia, radiation skin injury [reported term radiation dermatitis], and nausea. PK of prexasertib was consistent with previously published data following prexasertib monotherapy. Overall response rate in Parts A and B was 71.4% and 83.3%, respectively. The small number of patients and follow-up limits the interpretation of efficacy data. Conclusion: This study did not establish a safe dose of cisplatin-radiotherapy. However, it demonstrates the proof-of-principle that prexasertib could be safely combined with cetuximab-radiotherapy. These data will provide the basis to leverage the potential radio-sensitization properties of a CHK1 inhibitor in combination with radiation or other targeted agents in a variety of therapeutic settings.